Hubungan Hukum Internasional dengan Hukum Nasional - Rafael Satria Perdana Widyatma; Elza Qorina Pangestika (Mathematics Education Study Program, 2025)
National law has its own meaning for each nation in the scope of world regulations and universal society. International law is one part of the law that regulates the implementation of international law, international law itself regulates relations between nations, regulates conditions that are in dispute or communication, and provides rights and obligations to each nation. International law has two sources of law, namely formal legal sources and material legal sources. The agreement of national law on Universal Law means that National Law must be in harmony with Universal Law. Based on the importance of international relations, it is very important to have a law that is expected to be able to resolve all problems arising from international relations.